2020
DOI: 10.3390/jcm9051310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dysmetabolisms and Comorbidities on the Efficacy and Safety of Biological Therapy in Chronic Inflammatory Joint Diseases

Abstract: In the present study we evaluated how systemic arterial hypertension (SAH), dyslipidemia and diabetes mellitus influence the efficacy, safety and retention rate of biological disease-modifying anti-rheumatic drug (bDMARD) treatment in rheumatic musculoskeletal disorders (RMDs). The charts of RMD patients treated with the first-line bDMARD were reviewed, collecting data on safety, efficacy and comorbidities at prescription (baseline, BL), after 6 months (6M) and at last observation on bDMARD (last observation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Patient-centered care and the importance of psychosocial domains are increasingly recognized in the management strategy of PsA [ 2 ]. This paradigm stems from the observations that, on an individual level, the impact of disease extends beyond the skin and joint [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. It has been shown that achieving minimal disease activity in PsA leads to better quality of life and productivity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient-centered care and the importance of psychosocial domains are increasingly recognized in the management strategy of PsA [ 2 ]. This paradigm stems from the observations that, on an individual level, the impact of disease extends beyond the skin and joint [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. It has been shown that achieving minimal disease activity in PsA leads to better quality of life and productivity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%